Pemberdayaan Ibu-Ibu untuk Mengoptimalisasikan Lahan Pekarangan Rumah Desa Banjaran - Pipin Supinah; Alifah Syahfitri; Istie Sekartining Rahayu (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Pertanian Bogor, 2020)
The yard optimization program can have two benefits at the same time, namely increasing the economic value and the value of food security. The purpose of this activity is to socialize to the community the importance of optimizing the plot of land to increase economic value and food security on a family scale. The method used in this activity is a lecture followed by a question and answer session, in the last session there was a distribution of vegetable seeds such as tapai that can be planted in the family yard. The results of this day's activity the community, especially housewives, understood the importance of optimizing the family yard by growing it with various kinds of family needs such as vegetables and family medicinal plants. . Keywords: Banjaran village, land yard, empowerment